Identification of Cell-Cell Communications by Single-Cell RNA Sequencing in End Stage Renal Disease Provides New Insights into Immune Cell Heterogeneity - Zhang R; Liu X; Ma Y; Cheng L; Ren Y; Li R (Dove Medical Press, 2023)
Ruijing Zhang,1- 3 Xinyan Liu,2 Yuehong Ma,1,3 Lijuan Cheng,2 Yi Ren,1,3 Rongshan Li1,3 1Department of Nephrology, The Fifth Hospital of Shanxi Medical University, Taiyuan, People's Republic of China; 2Department of Nephrology, The Second Hospital of Shanxi Medical University, Taiyuan, People's Republic of China; 3Department of Nephrology, Shanxi Provincial People's Hospital, Taiyuan, People's Republic of ChinaCorrespondence: Rongshan Li, Email rongshanli@126.comObjective: Impaired immune system characterized by low-grade inflammation is closely associated with kidney chronic kidney disease (CKD) progression. To reveal the alterations of the function, component, and intercellular communication of immune cells during the progression of CKD.Patients and Methods: We conducted a case-control study enrolling regular hemodialysis patients and healthy controls. Clinical data, serum and peripheral blood mononuclear cell (PBMC) samples were collected. Flow cytometry and single-cell RNA sequencing were performed to quantitatively analyze the immune cell subsets and T-cell subsets of PBMCs. scRNA data of GSE140023 containing mouse unilateral ureteral obstruction (UUO) models were analyzed the heterogeneity of immune cells.Results: Overall reduction in peripheral blood lymphocyte subsets in patients with end-stage renal disease (ESRD) was observed. A higher ratio of Th17/Treg, Th1/Treg, and b-cell/Treg in the ESRD group was associated with a decrease in eGFR, PTH, and ferritin. Among T cell subsets identified by scRNA analysis, Th17 cells were significantly increased in the ESRD and UU0 group. TFH, Th1, and Th2 cells are located at the final stage in the developmental tree, while Treg and memory CD8+ T cells are at the beginning site. Early developmental differentiation of Th17, Th1, and Tfh cells was observed in the ESRD and UUO group. Analysis of intercellular communication between t-cell subpopulations identified two major input and output signaling pathways: the CD40 and macrophage inhibitory factor (MIF) pathways. The MIF signaling pathway primarily mediates intercellular communication among th17 effects, CD8+ t-cell, and Th17-Treg in the ESRD group, the serum level of MIF showed significant upregulation, which was closely related to Th17/Treg cells.Conclusions: A global immune imbalance was closely associated with the deterioration in renal function and complication development. The MIF signaling pathway mediates Th17/Treg communication and promotes the trans-differentiation of Treg cells to Th17 cells in CKD progression.Keywords: chronic kidney disease, end-stage renal disease, immune suppression, T cell plasticity, cell- cell communication